(untitled) (Veterinary Science, 2017)
The objective of this work was to study the main quality parameters of horse meat.We determined surface color, texture, moisture content, water activity, pH, drainage, losses during cooking and microbiological quality of samples of horsemeat for the Longissimus dorsi muscle, 48 hours postmortem.The surface colour was quantified based on the coordinates L*, a*, b* of CIE scale, using a Minolta colorimeter CR300 Series.The texture was measured with aTA-XT2 texturemeter Stable Micro Systems Ltd, using Warner-Bratzler probe.The surface colour values were L *= 34.05, a *= 18.85 and b = 9.25, only the lightness (L *) was slightly lower than beef, thus indicating darker meat.As for texture, equine muscle showed 15% greater shear strength. The values of moisture content (%), aw, pH and cooking losses were 74.3%, 0.982, 5.37 and 28% respectively, and none of the cases showed significant differences with the control. The exudate (drip) in 24 hours when stored at 4 º C was 2.37%.This value is within the range of those reported by authors for beef. In relation to microbiological quality, initial counts were made total mesophilic microorganisms and Enterobacteriaceae from equine meat surfaces, with values of 76.36 CFU/g and 74.6 CFU/g respectively.These results are within the range allowed by the CAA, this food can be considered as optimal for consumption.According to the results we can conclude that horse meat would be a highly viable for human consumption replaces beef.